Anions as Triggers in Controlled Release Protocols from Mesoporous Silica Nanoparticles Functionalized with Macrocyclic Copper(II) Complexes. Issue 39 (17th August 2016) - El Sayed, Sameh; Milani, Michele; Milanese, Chiara; Licchelli, Maurizio; Martínez‐Máñez, Ramón; Sancenón, Félix
Abstract: Three different mesoporous silica nano‐sized materials (SC1, SC2, andSC3 ), loaded with [Ru(bipy)3 ] 2+ dye (bipy=bipyridine) and functionalized on the external surface with three macrocyclic copper(II) complexes (C1, C2, andC3 ), were synthesized and characterized. WhenSC1, SC2, andSC3 were suspended in water, the entrapped [Ru(bipy)3 ] 2+ dye was free to diffuse from the inner pores to the solution. However, addition of anions induced certain degrees of pore blockage, with subsequent dye release inhibition. Small monovalent and divalent anions were unable to induce complete pore blockage, whereas bulky and highly charged anions induced marked reductions in [Ru(bipy)3 ] 2+ delivery. The best [Ru(bipy)3 ] 2+ delivery inhibitors were ATP and hexametaphosphate anions. Inhibition was ascribed to the interaction of the anions with the grafted Cu II complexes on the surface of theSC1, SC2, andSC3 supports. The hexametaphosphate anion was selected to prepare two capped materials (SC1‐mPh andSC3‐mPh ). Studies of the [Ru(bipy)3 ] 2+ dye release from solidsSC1‐mPh andSC3‐mPh alone and in the presence of a collection of selected anions (HS −, F −, Br −, Cl −, I −, CN −, HPO4 2−, AcO −, citrate, NO3 2−, HCO3 −, SO4 2−, and S2 O8 2− ), amino acids (alanine and histidine), thiol‐containing biomolecules (cysteine, methylcysteine, homocysteine, and glutathione (GSH)), and oxidants (H2 O2 ) were performed. None of the chemicals tested, except hydrogen sulphide, was able to induce remarkable cargo delivery in both solids. The observed dye release was ascribed to a demetalation reaction of theC1 andC3 complexes induced by the hydrogen sulphide anion. Abstract : Bulky anions as stoppers : Three hybrid materials based on nano‐sized mesoporous silica, loaded with a dye, and functionalized on the external surface with macrocyclic complexes were prepared and characterized. Dye release in water was strongly inhibited by bulky and highly charged anions (e.g., hexamethaphosphate) owing to their multiple interactions with metal ions on the surface, whereas small anionic species were not able to hinder the delivery process (see scheme).